The management of adult psychiatric emergencies in low-income and middle-income countries: a systematic review. (June 2015) - Nadkarni, Abhijit; Hanlon, Charlotte; Bhatia, Urvita; Fuhr, Daniela; Ragoni, Celina; de Azevedo Perocco, Sérgio Luiz; Fortes, Sandra; Shidhaye, Rahul; Kinyanda, Eugene; Rangaswamy, Thara; Patel, Vikram
Summary: The aim of this Review is to identify effective interventions and treatment guidelines to manage common types of psychiatric emergencies in non-specialist settings in low-income and middle-income countries. Mental health specialist services in low-income and middle-income countries are scarce. We did a systematic review of interventions for psychiatric emergencies and a literature search for low-income and middle-income-specific treatment guidelines for psychiatric emergencies. A dearth of high-quality guidelines and contextualised primary evidence for management of psychiatric emergencies in low-income and middle-income countries exists. Filling these gaps in present guidelines needs to be an urgent research priority in view of the adverse health and social consequences of such presentations and the present drive to scale up mental health care.